2018
DOI: 10.1021/acssensors.7b00764
|View full text |Cite
|
Sign up to set email alerts
|

Visual Sensor for Sterilization of Polymer Fixtures Using Embedded Mesoporous Silicon Photonic Crystals

Abstract: A porous photonic crystal is integrated with a plastic medical fixture (IV connector hub) to provide a visual colorimetric sensor to indicate the presence or absence of alcohol used to sterilize the fixture. The photonic crystal is prepared in porous silicon (pSi) by electrochemical anodization of single crystal silicon, and the porosity and the stop band of the material is engineered such that the integrated device visibly changes color (green to red or blue to green) when infiltrated with alcohol. Two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…1a). Amongst many, the simplest method is the formulation of polymer-infiltrated pSi (A), where the polymer invades the entire pore of pSi [22][23][24][25]. After the nano-sized pores are filled with polymers, the formulations can be intensified by the covalent attachment between the pore walls and polymers.…”
Section: Hybrid System Of Psinps and Polymersmentioning
confidence: 99%
“…1a). Amongst many, the simplest method is the formulation of polymer-infiltrated pSi (A), where the polymer invades the entire pore of pSi [22][23][24][25]. After the nano-sized pores are filled with polymers, the formulations can be intensified by the covalent attachment between the pore walls and polymers.…”
Section: Hybrid System Of Psinps and Polymersmentioning
confidence: 99%
“…In [73,100], the authors reported on the visual colorimetric sensing techniques suitable for (bio)molecule detection. Photonic polymer modified PSi templates have shown prospective results for non-pathogenic E. coli and isopropanol alcohol detection.…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%
“…These photonic PSi/polymer composites have also shown enhanced sensitivity to E. coli when compared with all-polymer photonic sensors. This can be attributed to differences in their wettability, which affects E. coli adhesion [100]. Ramakrishan et al reported on a PSi microcavity for autoimmune disease detection based on H 2 B antigens or antibodies quantification via red, green, and blue (RGB) spectral analysis (Figure 4).…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%
“…One of the most promising materials in this field is porous silicon (PSi), which is a widely used semiconductor with exceptional photonic [1], structural and electronic properties. Due to its unique properties and diverse structural design, PSi is an ideal candidate not only for optoelectronic devices [2,3] and novel drug delivery systems but also for chemical and biosensing applications [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%